Respon Pertumbuhan dan Hasil Tiga Varietas Padi Gogo (Oryza sativa L.) pada Berbagai Kondisi Cekaman Kekeringan - Pasya Salsadilla; Kacung Hariyono (Berkala Ilmiah Pertanian, 2022)
Drought has a direct impact on the agricultural sector. Dry land is one type of marginal land, because drought causes various negative impacts on plants. The long drought causes the water requirement for plants to stagnate so that the plants experience stress or experience drought stress conditions. Drought stress is an environmental condition where plants do not receive sufficient water intake, so that plants cannot carry out the process of growth and development optimally and production decreases. One way that can be done on the problem of drought is to identify several plant varieties to see the response and ability of plants to survive under stress conditions. The purpose of this study was to determine the effect of drought conditions, to determine the effect of upland rice varieties and the interactions that occur between upland rice varieties and various drought stress conditions on growth and yield. The research method used was a Factorial Completely Randomized Design (CRD). The first factor is 100% field capacity, 80% field capacity, 60% field capacity and 40% field capacity, while the second factor is Inpago 8 variety, Inpago 9 variety and Situ bagendit variety. The results of the research conducted showed that the level of drought stress had an effect on the growth and yield of upland rice plants. The higher the drought conditions experienced by plants, the growth and yields on plants are much lower and yields are less. This is because the availability of water for plants is not sufficient. The higher the drought conditions experienced by the plant, the longer the root length of the plant. This is because plants that experience drought stress in the vegetative phase will inhibit crown growth and increase root growth.